Subthreshold Micropulse Laser vs. Conventional Laser for Central Serous Chorioretinopathy: A Randomized Controlled Clinical Trial - Zhou, Lijun; Lai, Kunbei; Jin, Ling; Huang, Chuangxin; Xu, Fabao; Gong, Yajun; Li, Longhui; Zhu, Zhe; Lu, Lin; Jin, Chenjin (Frontiers in Medicine, 2021)
Purpose: To investigate the effectiveness and safety of 577nm subthreshold micropulse laser (SML) on acute central serous chorioretinopathy (CSC). Methods: One hundred and ten patients with acute CSC were randomized to receive SML or 577nm conventional laser (CL) treatment. Optical coherence tomography and best-corrected visual acuity (BCVA) were performed before and after treatment.Results: At 3 months, the complete resolution of subretinal fluid (SRF) in 577nm SML group (72.7%) was lower than that in CL group (89.1%) (Unadjusted RR, 0.82; P=0.029), but it was 85.5% VS 92.7% at 6 months (unadjusted RR, 0.92; P=0.221). The mean LogMAR BCVA significantly improved, and the mean central foveal thickness (CFT) significantly decreased in the SML group and CL group (all P<0.001) at 6 months. But there was no statistical difference between the two groups (all P>0.05). In the SML group, obvious retinal pigment epithelium (RPE) damage was shown only in 3.64% at 1 month but 92.7% in the CL group (P<0.001). Conclusions：Although 577nm SML has a lower complete absorption of SRF compared with 577nm CL for acute CSC at 3 months, it is similarly effective as 577nm CL on improving retinal anatomy and function at 6 months. Importantly, 577nm SML causes less damage to the retina.